Electrophoretic deposition and characterization of Eu2O3 nanocrystalCarbon nanotube heterostructures - Mahajan, S. V.; Cho, J.; Shaffer, M. S. P.; Boccaccini, Aldo R.; Dickerson, J. H. (Journal of the European Ceramic Society, 2010)
Electrophoretic deposition (EPD) was employed to assemble a layered architecture of multi-walled carbon nanotube (CNT) mats and europium oxide nanocrystal (NC) films. CNT mats were produced via low field-high current EPD, while NC films were deposited via high field-low current EPD. The two EPD techniques were integrated in an alternating sequence to create CNT mat-NC film-CNT mat heterostructures with sharp interfaces. The EPD techniques produced uniformly porous CNT mats and densely packed NC films. Morphology and surface coverage of the films were investigated using scanning electron microscopy (SEM), while elemental characterization was performed using energy dispersive spectroscopy (EDS). Photoluminescence (PL) spectroscopy measurements were conducted on the NC suspension and the NC films to confirm film formation. Capacitance-voltage (CV) measurements were performed to probe energy-storage capabilities of the layered architecture. © 2009 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.electr_5
Keywords: Eu; Films; Nanocomposites; Nanotubes; Suspensions